Modelling of Reinforced Concrete Framed Structures Interacting with a Shallow Tunnel. (2016) - Boldini, Daniela; Losacco, Nunzio; Bertolin, Sara; Amorosi, Angelo
Abstract: This paper deals with the numerical analysis of tunnelling-induced settlements on concrete framed structures founded on strip footings. In particular, a single frame with a variable number of storeys is taken into account in the present study, with an orientation perpendicular to the tunnel axis and a null eccentricity. The Finite Element simulations, carried out in three- dimensions with the code Abaqus, highlight the influence of the building stiffness and weight on the displacement field and provide an insight into the loading transfer mechanism occurring in the structural elements during tunnel excavation.